ANTECEDENT ANALYSIS OF JOB SATISFACTION IN THE HOSPITALITY INDUSTRY SECTOR IN BATAM CITY - Ridhayati Farid; Jonathan Jonathan; Siti Rohani (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study analyzes factors influencing the job satisfaction of hotel employees in the tourism sector, focusing on innovation and employees’ active role in shaping their work environment. The study involves employees of 1- to 3-star hotels in Batam City, with 352 respondents selected through probability sampling. Data were collected through a 33-item Google Form questionnaire and analyzed using the PLS method with SmartPLS 4.0. The results show that job crafting and innovative work behavior do not directly affect job satisfaction but influence organizational support and employee engagement. Organizational support and employee engagement significantly affect job satisfaction and act as mediators in the relationship between job crafting and innovative work behavior with job satisfaction. Thus, employee job satisfaction cannot be built solely through job crafting or innovation but must be supported by organizational support and employee engagement. Keywords: Employee Engagement; Innovative Work Behavior; Job Crafting; Job Satisfaction; Organizational Support